Modular composition of multiple applications with architectural event modules. (16th January 2017) - Malakuti, Somayeh
Summary: A complex software system is usually developed as a system of systems (SoS's) in which multiple constituent applications are composed and coordinated to fulfill desired system‐level requirements. To facilitate the interoperability of the constituent applications, they must be augmented with suitable coordination‐specific interfaces, through which they can participate in coordinated interactions. To increase the reusability of the applications and to increase the comprehensibility of SoS's, suitable mechanisms are required to modularize the coordination rules and interfaces from the constituent applications. We introduce a new abstraction named as architectural event modules (AEMs), which facilitates defining constituent applications and desired coordination rules as modules of SoS's. AEMs modularly augment the constituent applications with event‐based interfaces to let them participate in coordinated interactions. We introduce the EventArch language in which the concept of AEMs is implemented, and illustrate its suitability using a case study in the domain of energy optimization. Copyright © 2017 John Wiley & Sons, Ltd.